Teaching Skills of English Language Teachers in the Primary Stage from Their Point of View - Jamal khssif Alalway ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The aim of the research is to identify the level of teaching skills of English language teachers in the primary stage from their point of view. The research sample consisted of (45) male and female English language teachers in Maysan with (23 teachers) and (22 female teachers), and the researcher built His research tool consists of a set of standards for teaching skills amounting to (38 items) distributed over three skill areas, which are the skill (planning, implementation, evaluation) in teaching. The research indicated that the level of teaching skills of English language teachers is average, and its arrangement according to the data obtained was (the skill of implementing the lesson) in the first place, then (the assessment skill) in the second place, and then (the skill of teaching planning) in the third place, and the results showed that only In the skill (planning) in favor of males, and there are also no statistically significant differences among English language teachers according to the school’s place in my skills (planning and evaluation), and there is a statistical difference in the skill (implementation) only, and at the end of the research the researcher presented a set of recommendations and suggestions at light search resultsDOI /10.54633/2333-021-042-008